2021
DOI: 10.3390/cosmetics8040092
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Aspects of Skin Collagen Fiber Turnover and Functioning

Abstract: One of the most important functions of the skin, i.e., protection from mechanical damage, is ensured by collagen fibers and their interaction with other elements in the extracellular matrix. Collagen fiber turnover is a complex multi-stage process. At each stage, a disruption may occur, leading to a decrease in the mechanical properties of the connective tissue. Clinically, collagen formation disorders manifest themselves as increased flabbiness and looseness of the skin and as early signs of facial aging. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 108 publications
0
1
0
1
Order By: Relevance
“…The results that genes expressed in the epidermal basal layer and dermis were significantly upregulated in the SNF dermal/epidermal model compared with the Collagen dermal/epidermal model suggested that while fibroblasts in the Collagen dermal/epidermal model were covered by collagen, fibroblasts in rigid SNF were highly proliferative. hCOL1, hCOL3, and hCOL4 are associated with skin elasticity [20,[48][49][50]. Therefore, upregulated expression of hCOL1, hCOL3, and hCOL4 in SNF dermal/epidermal model means that it has high functions as a dermal/epidermal skin model.…”
Section: Discussionmentioning
confidence: 99%
“…The results that genes expressed in the epidermal basal layer and dermis were significantly upregulated in the SNF dermal/epidermal model compared with the Collagen dermal/epidermal model suggested that while fibroblasts in the Collagen dermal/epidermal model were covered by collagen, fibroblasts in rigid SNF were highly proliferative. hCOL1, hCOL3, and hCOL4 are associated with skin elasticity [20,[48][49][50]. Therefore, upregulated expression of hCOL1, hCOL3, and hCOL4 in SNF dermal/epidermal model means that it has high functions as a dermal/epidermal skin model.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased collagen numbers induce myofibroblast apoptosis as a result of these cytokine activities (Potekaev et al, 2021). When the researchers compared scar fibroblasts with their normal counterparts, they found that collagenase mRNA was reduced and their ability to digest soluble collagen was also reduced (Zhu et al, 2013).…”
Section: Volume 35 Issue 2 (2024)mentioning
confidence: 99%
“…This natural polymer, representing 25% of the dry weight of all the body tissues including skin, is synthesized under the influence of diet, environment and age. However, its synthesis depends also on the state of hormonal background, the inherent genetic sequences and the epigenetic regulation of the gene's activity, which encode key proteins and enzymes during the collagen formation [80,81]. To this end, it is important to remember the many essential roles played by the previously reported ECM which, produced principally from fibroblasts, provides structural support for cells and tissues, modulating cell morphology, proliferation, migration and also gene expression [82,83].…”
Section: Collagenmentioning
confidence: 99%